Nanomaterials and paper-based electrochemical devices: merging strategies for fostering sustainable detection of biomarkers. Issue 44 (28th July 2022) - Caratelli, Veronica; Di Meo, Erika; Colozza, Noemi; Fabiani, Laura; Fiore, Luca; Moscone, Danila; Arduini, Fabiana
Abstract : This review aims to analyze how the paper material offers unique and polyvalent properties to bridge together multiple uses of nanomaterials and develop electrochemical biosensors for application in the biomedical field. Abstract : In the last few decades, nanomaterials have made great advances in the biosensor field, thanks to their ability to enhance several key issues of biosensing analytical tools, namely, sensitivity, selectivity, robustness, and reproducibility. The recent trend of sustainability has boosted the progress of novel and eco-designed electrochemical paper-based devices to detect easily the target analyte(s) with high sensitivity in complex matrices. The huge attention given by the scientific community and industrial sectors to paper-based devices is ascribed to the numerous advantages of these cost-effective analytical tools, including the absence of external equipment for solution flow, thanks to the capillary force of paper, the fabrication of reagent-free devices, because of the loading of reagents on the paper, and the easy multistep analyses by using the origami approach. Besides these features, herein we highlight the multifarious aspects of the nanomaterials such as (i) the significant enlargement of the electroactive surface area as well as the area available for the desired chemical interactions, (ii) the capability of anchoring biorecognition elements on the electrode surface on the paper matrix, (iii) the improvement of the conductivity of the cellulose matrix, (iv) the functionality of photoelectrochemical properties within the cellulose matrix, and (v) the improvement of electrochemical capabilities of conductive inks commonly used for electrode printing on the paper support, for the development of a new generation of paper-based electrochemical biosensors applied in the biomedical field. The state of the art over the last ten years has been analyzed highlighting the various functionalities that arise from the integration of nanomaterials with paper-based electrochemical biosensors for the detection of biomarkers.